The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1017/s0031182019000672
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic activity of plants against gastrointestinal nematodes of goats: a review

Abstract: The gastrointestinal nematodes (GIN) stand out as an important cause of disease in small ruminant, especially on goat farm. Widespread resistance to synthetic anthelminthics has stimulated the research for alternative strategies of parasite control, including the use of medicinal plants. The present work summarizes the in vitro and in vivo studies of plants with activity against GIN of goats, focusing on the description of chemical constituents related to this effect. This review retrieved 56 scientific articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 88 publications
(110 reference statements)
2
29
0
3
Order By: Relevance
“…Our previous studies found that the effect of medicinal plants on GIN-infected sheep depended on the variety and synergy of polyphenols in medicinal plants and on the combination of bioactive compounds that together had an effect contributing to pharmacological efficacy [ 7 , 8 , 9 , 10 ]. Most studies conducted mainly with the use of medicinal plants in ruminants, however, have generally found lower effectiveness of plant materials against parasites in vivo compared to in vitro [ 11 , 12 ]. The presence of a GIN infection also disturbs the mineral metabolism of ruminants, and mineral deficiencies in nutrition are associated with increased GIN burdens in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies found that the effect of medicinal plants on GIN-infected sheep depended on the variety and synergy of polyphenols in medicinal plants and on the combination of bioactive compounds that together had an effect contributing to pharmacological efficacy [ 7 , 8 , 9 , 10 ]. Most studies conducted mainly with the use of medicinal plants in ruminants, however, have generally found lower effectiveness of plant materials against parasites in vivo compared to in vitro [ 11 , 12 ]. The presence of a GIN infection also disturbs the mineral metabolism of ruminants, and mineral deficiencies in nutrition are associated with increased GIN burdens in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Compuestos fenólicos: De los cuales se han identificado 8,000 estructuras (42) y que representan el grupo de MSP más estudiados en lo que se refiere a las propiedades bioactivas en contra de los NGI en pequeños rumiantes. Dentro de este grupo, los taninos condensados han recibido una atención especial debido a su actividad AH y su presencia en varias especies de plantas presentes en sistemas de vegetación nativa a nivel mundial (43,44,45).…”
Section: Metabolitos Secundarios De Las Plantas Y Sus Propiedades Antihelmínticasunclassified
“…Undoubtedly the more-studied PSC in terms of ruminant nutrition and AH activity are the CT [ 13 , 27 , 28 , 29 , 30 ]. Nonetheless, it is known that other PSC such as flavonoids, saponins, terpenes, alkaloids, hydrolysable tannins, among others, could influence the physiology of both ruminants and nematodes [ 34 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ]. Hence, considering the plethora of plant species and PSC present in the LDF, we have a wide avenue of future research.…”
Section: Final Remarks and Implicationsmentioning
confidence: 99%
“…The majority of studies related to the assessment of nutraceutical properties of plants have been performed using in vitro tests [ 34 , 35 ], which could be related to their lower cost, rapid turnover and the possibility of obtaining and testing the activity of specific PSC through the use of solvents [ 148 , 152 ]. On the contrary, during in vivo trials, intake of different levels and concentrations of both nutrients and PSC is unavoidable when experimental plants are consumed (the higher the number of plants, the harder the possibility of interpreting the results).…”
Section: Final Remarks and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation